The in silico identification and characterization of a bread wheat/Triticum militinae introgression line - Abrouk, Michael; Balcárková, Barbora; Šimková, Hana; Komínkova, Eva; Martis, Mihaela M; Jakobson, Irena; Timofejeva, Ljudmilla; Rey, Elodie; Vrána, Jan; Kilian, Andrzej; Järve, Kadri; Doležel, Jaroslav; et al. (Plant biotechnology journal, 2017)
The capacity of the bread wheat (Triticum aestivum) genome to tolerate introgression from related genomes can be exploited for wheat improvement. A resistance to powdery mildew expressed by a derivative of the cross-bread wheat cv. Tähti × T. militinae (Tm) is known to be due to the incorporation of a Tm segment into the long arm of chromosome 4A. Here, a newly developed in silico method termed rearrangement identification and characterization (RICh) has been applied to characterize the introgression. A virtual gene order, assembled using the GenomeZipper approach, was obtained for the native copy of chromosome 4A; it incorporated 570 4A DArTseq markers to produce a zipper comprising 2132 loci. A comparison between the native and introgressed forms of the 4AL chromosome arm showed that the introgressed region is located at the distal part of the arm. The Tm segment, derived from chromosome 7G, harbours 131 homoeologs of the 357 genes present on the corresponding region of Chinese Spring 4AL. The estimated number of Tm genes transferred along with the disease resistance gene was 169. Characterizing the introgression's position, gene content and internal gene order should not only facilitate gene isolation, but may also be informative with respect to chromatin structure and behaviour studies.
Keywords: Base Sequence; Ascomycota; Triticum; nemoci rostlin; DNA, Plant; počítačová simulace; mapování chromozomů; chromosome rearrangement; Chromosome Mapping; odolnost vůči nemocem; Disease Resistance; chléb; Chromosomes, Plant; Translocation, Genetic; chromozomy rostlin; chromosome translocation; Computer Simulation; rostlinné geny; Plant Diseases; DNA rostlinná; linkage drag; sekvence nukleotidů; Microsatellite Repeats; genetické markery; translokace genetická; pšenice; comparative analysis; mikrosatelitní repetice; Genes, Plant; GenomeZipper; alien introgression; Bread; Genetic Markers